(untitled) (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to improve the ability to recognize number symbols from 1 to 10 through the use of Number Board media in children with mild intellectual disabilities. The approach used in this research is quantitative, with an experimental methodology in the form of a single-subject (SSR) design using an A-B model. The subject of this study was a fourth-grade student at SLBN 1 Linggo Sari Baganti who had difficulty recognizing number symbols. The data collection technique used was a test, with instruments consisting of questions requiring the student to name and point to number symbols. The data analysis technique employed in this study was visual graph analysis. The research was conducted over 12 meetings,3 meetings during the baseline phase with percentage scores of 10%, 10%, and 10%, and 9 meetings during the intervention phase with percentage scores of 40%, 50%, 60%, 70%, 80%, 90%, 100%, 100%, and 100%. The improvement was accompanied by a positive trend in the direction of the data and significant stability in the results. This study shows that the Number Board media can help children recognize number symbols in addition operations in a concrete, simple, and enjoyable way.